Voices Revealed Arab Women Novelists, 1898-2000 - Šaʿbān, Buṯaina 1953- (Lynne Rienner Publishers, 2022)
Spanning more than a century, this systematic analysis brings to the forefront a dazzling array of novels by Arab women writers